Pengaruh Perbandingan Tepung Talas Kimpul (Xanthosoma sagittifolium) Termodifikasi Autoclaving-Cooling dengan Terigu terhadap Karakteristik Mie Basah - Ningrum, Ni Nengah Widya; Putra, I Nengah Kencana; Wiadnyani, Anak Agung Istri Sri (Jurnal Ilmu dan Teknologi Pangan (ITEPA); Vol 14 No 2 (2025): Jurnal ITEPA, 2025)
Noodles are one of the popular food products in Indonesia. The use of autoclaving-cooling modified cocoyam flour as a wheat substitute in making wet noodles can be an alternative in efforts to diversify food based on local ingredients. This study aims to optimize the ratio of wheat and modified cocoyam flour in wet noodle formulations. This study used a complete randomized design (CRD) with five treatments of wheat and modified cocoyam flour ratio, namely 100% : 0%, 85% : 15%, 70% : 30%, 55% : 45%, and 40% : 60%, with three replicates. The results showed that wheat substitution using modified cocoyam flour significantly affected chemical properties (moisture content, ash content, protein, fat, carbohydrates, and crude fiber), physical properties (water absorption, elongation, cooking loss, cooking time), and organoleptic parameters. The best formulation was obtained on 30% wheat substitution, which produced wet noodles with 34.85% moisture content, 1.80% ash content, 7.28% protein content, 0.79% fat content, 55.25% carbohydrate content, 1.56% crude fiber content, 94.72% water absorption, 20.61% elongation, 10.19% cooking loss, and 3.33 minutes cooking time. Organoleptically, the resulting wet noodles have a fairly elastic texture, a slightly brownish color, and an overall acceptance rate in the "somewhat liked" category. Thus, autoclaving-cooling modified cocoyam flour has the potential to be a wheat substitution ingredient in the production of wet noodles with an optimal formulation at a substitution rate of 30%. Keywords: wet noodles, cocoyam, modified flour, autoclaving-cooling